Effect of nursing interventions based on the Kano model on symptom relief and parental psychological behavior in children with febrile seizures - Zhu, Zaiyun; Chen, Liping; Li, Kai (Frontiers in Psychology, 2023)
Abstract Purpose: To analyse the effect of nursing interventions based on the Kano model on symptom relief in children with febrile seizures (FS) and parental psychological behaviour. Methods: 104 children with FS admitted to our hospital from January 2021 to April 2022 were studied. All children were divided into 2 groups according to their care regimen during treatment. Children who received general nursing interventions were enrolled in the general group (n=52) and children who received nursing interventions based on the Kano model were enrolled in the Kano group (n=52). In this study, an investigation was first conducted to analyse the attributes of the caring care service needs of the families of children with FS. Then, we compared 4 aspects of symptom relief during the hospital stay of the 2 groups of children, including frequency of FS episodes, time to fever reduction, time to cessation of convulsions and time to recovery of consciousness. The Parent Symptom Questionnaire (PSQ) was used to assess the psychological behaviour of the two groups of children during their stay in hospital. The Chinese perceived stress scale (CPSS) and the symptom checklist 90 (SCL-90) were used to assess the psychological behaviour of the two groups of their families during the children's hospitalisation. Finally, a questionnaire was administered on the satisfaction of this nursing intervention. Results: In terms of symptom relief, the children in the Kano group had less frequent FS episodes than the conventional group, and the time to fever reduction, cessation of convulsions and recovery of consciousness were all earlier than in the conventional group (P<0.05). In terms of children's psychological behaviour, the impulsivity-hyperactivity, anxiety, hyperactivity index and learning problems scores in the PSQ of the children in the Kano group were lower than those in the general group after the intervention (P<0.05). Conclusion: The implementation of the nursing interventions based on the Kano model for children with FS was successful in dramatically reducing the clinical signs and symptoms of the children and meeting the psychological and behavioural needs of the children and their families.